Eksistensi Mahasiswa Terhadap Kemampuan Literasi dan Numerasi Melalui Program Kampus Mengajar Angkatan 6 di SMP Mardi Siwi Kota Surabaya - Zakaria, Azar; Sunarti, Titin (Universitas Negeri Surabaya, 2025)
Literacy skills include the ability to utilize various sources to understand information or ideas through listening, reading, and viewing activities, as well as conveying ideas using various media in oral or written form, according to the context. This study aims to improve the quality of education in schools and develop students' soft skills to be better prepared to face the world of work. Through this program, students are able to improve their teaching skills and help improve literacy and numeracy skills. Data acquisition techniques were obtained descriptively quantitatively through interview techniques and a humanistic approach to the Mardi Siwi community in the form of implementing several learning media related to several subjects at the junior high school level. Overall, these data show that most students made positive progress in both Numeracy and Literacy. However, there were also some participants who showed variation in results, with some experiencing significant improvements, while others experienced declines or stability in final results. This shows the importance of adjusting learning strategies to meet the individual needs of students and ensure consistent improvement in all aspects of learning. The total increase in Numeracy was around 56.36%, while the total increase in Literacy was around 36.36%.